A new intensive conditioning regimen for allogeneic hematopoietic stem cell transplantation in patients with refractory or relapsed acute myeloid leukemia. Issue 17 (April 2018) - Wang, Jingbo; Zhao, Jie; Fei, Xinhong; Yin, Yuming; Cheng, Haoyu; Zhang, Weijie; Gu, Jiangying; Yang, Fan; Yang, Yixin; Xue, Song; Tian, Zhengqin; He, Junbao; et al.
Abstract : Abstract: To explore the efficacy, and safety of the intensive conditioning regimen consisting of cladribine, cytarabine (Ara-C), and granulocyte colony-stimulating factor (G-CSF) plus modified busulfan (Bu) combined with cytoxan (Cy) (BuCy), prior to allogeneic hematopoietic stem cell transplantation (allo-HSCT) in patients with refractory, or relapsed acute myeloid leukemia (R/R AML). Thirty-Six R/R AML patients scheduled to receive allo-HSCT were consecutively, enrolled in this prospective study, and treated using intensive conditioning regimen consisting of CLAG plus modified BuCy. Median follow-up duration was 11.25 (range 0.5 – 21.0) months and the last follow up date was August 15, 2017. All patients (100%) achieved white blood cell (WBC) recovery within a median time of 16.00 (13.25 – 18.00) days, and 34 of them (94%) attained platelet (PLT) recovery within a median time of 13.50 (9.25 – 19.75) days. Incidence of acute graft-versus-host disease (aGVHD) was 50.00%, with median time of 71.50 (41.00 – 401.25) days. Three patients developed Grade I; nine, Grade II; 5, Grade III; and 1, Grade IV aGVHD. The incidence of chronic GVHD (cGVHD) was 44.40%, with median time of 255.00 (120.00 – 390.00) days. Four patients developed limited cGVHD, and 12, extensive cGVHD. One-year accumulating leukemia free survival (LFS), and overall survival (OS) rates between 52.9 ± 8.8% to 69.4 ± 7.7%, respectively. Eighteen (50%) patients were infected with cytomegalovirus; 2 (5.6%), with Epstein-Barr virus (EBV), 7 (19.4%), with hemorrhagic cystitis; 13 (36.1%), with bacteria; and 8 (22.2%), with fungus. Intensive conditioning regimen of CLAG plus modified BuCy for allo-HSCT may be effective and well-tolerated in R/R AML patients.